A narrative literature review: Growing the workforce through increased fieldwork capacity in genetic counseling training programs. Issue 2 (30th October 2020) - Berninger, Taylor; Nusbaum, Rachel; Redlinger‐Grosse, Krista; Davis, Claire; Reiser, Catherine
Abstract: In response to mounting concerns regarding a perceived shortage of genetic counselors, the Genetic Counselor Workforce Working Group (WFWG) was established in 2013 to identify barriers to growth of the genetic counseling workforce. After completing a workforce analysis and confirming a shortage, the WFWG convened a strategic planning session in 2017 to identify goals and strategies that would increase the number of certified counselors to meet the current and future workforce demands and ensure access to genetic counselor services. Subcommittees were formed and charged with achieving assigned goals; one such subcommittee included a curriculum working group to build a dynamic and effective educational infrastructure to increase the number of genetic counselors graduated from accredited training program. This paper reports of progress of the WFWG Curriculum Subcommittee toward achieving this goal through a narrative literature review that identifies innovative education methods that help to increase capacity of fieldwork training, both in genetic counseling training programs and in other health professions. Of the five thematic areas identified in this study, four are analyzed for insight into building clinical capacity: systems/infrastructure, rotation structure/models, skill building, and novel techniques. While additional studies are needed to establish best practices in these thematic areas, there are several take‐aways that training programs can begin to utilize as they look to expand training opportunities. While growth of the genetic counseling workforce will continue to be a long‐term issue, programs should begin to think creatively and innovatively about how to reach beyond traditional fieldwork training formats to build capacity. The strategies explored in this paper offer feasible and untapped solutions that can help support efforts to establish a sustainable genetic counseling workforce.